2010
DOI: 10.1007/bf03324782
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in older adults: an early indicator of the aging process?

Abstract: ABSTRACT. The aim of this paper is to give an overview (Aging Clin Exp Res 2010; 22: 100-115)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 143 publications
6
162
5
4
Order By: Relevance
“…Although the concepts of frailty and functional capacity are different, it is necessary to understand the relationship between these two variables (17) . Studies indicate that factors intrinsically linked to frailty, such as low levels of physical activity, fatigue, gait speed, and decreased muscle strength, can be predictors of disability (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concepts of frailty and functional capacity are different, it is necessary to understand the relationship between these two variables (17) . Studies indicate that factors intrinsically linked to frailty, such as low levels of physical activity, fatigue, gait speed, and decreased muscle strength, can be predictors of disability (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that factors intrinsically linked to frailty, such as low levels of physical activity, fatigue, gait speed, and decreased muscle strength, can be predictors of disability (17)(18) . In this study, functional capacity achieved significant results in the three groups (p<0.001), suggesting the importance of maintaining functional capacity, not only in pre-frail and frail older adults, but also in non-frail older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a common problem in older adults and has been suggested as being a part of the normal aging process [37]. The higher prevalence of fatigue in PD, however, cannot be explained only by older age.…”
Section: Discussionmentioning
confidence: 99%
“…As most activities of daily living involve submaximal contractions, our observation of lower ME in mobility-impaired older adults has implications for daily energy cost and the experience of symptomatic fatigue in this population. Although it has been suggested that muscle fatigue may be related to symptomatic fatigue in frail older individuals (1), evidence for such a connection is lacking. It is possible that muscle ME may provide a physiological link between muscle and symptomatic fatigue, although further investigation is necessary.…”
Section: Perspectives and Significancementioning
confidence: 99%